Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting. (Policy Papers; Policy Paper ;, 2009)
Against the backdrop of a global economic crisis, the IMFC has underscored the Fund's central role in responding to its membership's needs and restoring prosperity and financial stability. The Fund has acted with alacrity-by overhauling its lending framework; mobilizing strong support and firm pledges toward a tripling of its resources; and continuing to strengthen the quality of its surveillance. The work program is heavy, reflecting the responsibilities assigned to the Fund by the international community and the needs of our membership.